2019
DOI: 10.1002/capr.12285
|View full text |Cite
|
Sign up to set email alerts
|

‘Momma bear wants to protect’: Vicarious parenting in practitioners working with disturbed and traumatised children

Abstract: Practitioners working with disturbed and neglected children and young people face many practical and personal challenges, including countertransference and secondary trauma reactions. One underexplored area is the practitioner requirement to negotiate with children's parents and to process feelings towards both parents and children. We explore the experiences of female counsellors and psychologists working with children and young adults in the UK mental health care sector, using an inductive thematic analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…As highlighted by Sleater and Scheiner (2020), participants' reflection in and on action (Yanow and Tsoukas 2009) was rooted in a relational context, resonating with the concept of "co-transference" (Sapriel 1998, p. 82) that emphasises the role of the practitioners' person in a co-constructed relationship (Tudor 2018). Whilst countertransference has emerged as a significant construct in trauma work, the parental-protective role reported by participants resonates with vicarious parenting as a specific type of dynamic wherein relational dynamics might intertwine with practitioners' and adolescents' attachment styles (Fixsen et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As highlighted by Sleater and Scheiner (2020), participants' reflection in and on action (Yanow and Tsoukas 2009) was rooted in a relational context, resonating with the concept of "co-transference" (Sapriel 1998, p. 82) that emphasises the role of the practitioners' person in a co-constructed relationship (Tudor 2018). Whilst countertransference has emerged as a significant construct in trauma work, the parental-protective role reported by participants resonates with vicarious parenting as a specific type of dynamic wherein relational dynamics might intertwine with practitioners' and adolescents' attachment styles (Fixsen et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a lack of an interagency support system in their organisational context would undermine clinicians' confidence in providing a safe therapeutic environment (Edwards and Karnilowicz 2013; McElvaney and Tatlow-G o l d e n 2 0 1 6 ) . A l t e r n a t i v e l y , a s a s u b t y p e o f countertransference, vicarious parenting would capture practitioners' parental feelings towards their young clients whilst dealing with systemic difficulties (Fixsen et al 2019). Therefore, by enhancing the understanding of the therapist's use of self with specific clients' presentations, therapistfocused qualitative evidence may optimise treatment guidelines (Heinonen and Nissen-Lie 2020).…”
mentioning
confidence: 99%
“…As physical intervention is on the rise (Watkins, 2021), HCSWs may be facing a difficult environment and struggle emotionally after being exposed to severe violent incidences (Eriksen et al, 2006) or experience 'emotional labour' (Hochschild, 1979), which refers specifically to the strain of moderating emotions during interactions with patients. Working with vulnerable young people has been reported to be associated with burnout (McFadden et al, 2015) and increased emotional distress (Fixsen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Staff-patient relations are important in young people's recovery narratives (Biering & Jensen, 2010;Hayes et al, 2019Hayes et al, , 2020. Some have even suggested that experiences of staff and patients are intertwined (Fixsen et al, 2020;Hawsawi et al, 2020), suggesting that patients are also sensitive to staff wellbeing, with some patients moderating their own behaviour in response to staff stress (Mistry et al, 2015). Therefore, job-stress, inadequate training, emotional labour and undervalued professional identity can go beyond the experiences of T4 HCSWs experience and retention, potentially influencing the therapeutic environment of the ward (Mistry et al, 2015) and the recovery of patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, whilst privacy and a secure therapeutic frame are necessary to centre the child's needs and develop trust (Kirkbride, 2021), excessive focus on these could conceal practitioners' desire to avoid the uncomfortable complexity of engaging with parents (Goodman, 2017; Siskind, 1997; Slade, 2008). Complexities include the following: the contagious helplessness of help‐seeking parents (Malberg, 2015); tension between holding confidentiality and supporting parents to develop understanding (Lowe, 2019); managing multiple or competing agendas (Malberg, 2015; Slade, 2008); powerful countertransferential feelings impacting real relationships with parents (Fixsen et al, 2019; Novick & Novick, 2011); and navigating the complex rivalries inherent in triadic relating (Goodman, 2017; Gvion & Bar, 2014). Grappling with, instead of avoiding, these inherent complexities may offer potential to harness the constructive, growth‐promoting and stabilising benefits of triangular relating within the parent–child–therapist triad (Friedman, 1991).…”
Section: Introductionmentioning
confidence: 99%